Beam properties within the momentum acceptance of a clinical gantry beamline for proton therapy. Issue 3 (4th February 2022) - Giovannelli, Anna Chiara; Maradia, Vivek; Meer, David; Safai, Sairos; Psoroulas, Serena; Togno, Michele; Bula, Christian; Weber, Damien Charles; Lomax, Antony John; Fattori, Giovanni
Abstract: Purpose: Energy changes in pencil beam scanning proton therapy can be a limiting factor in delivery time, hence, limiting patient throughput and the effectiveness of motion mitigation techniques requiring fast irradiation. In this study, we investigate the feasibility of performing fast and continuous energy modulation within the momentum acceptance of a clinical beamline for proton therapy. Methods: The alternative use of a local beam degrader at the gantry coupling point has been compared with a more common upstream regulation. Focusing on clinically relevant parameters, a complete beam properties characterization has been carried out. In particular, the acquired empirical data allowed to model and parametrize the errors in range and beam current to deliver clinical treatment plans. Results: For both options, the local and upstream degrader, depth‐dose curves measured in water for off‐momentum beams were only marginally distorted (γ(1%, 1 mm) > 90%) and the errors in the spot position were within the clinical tolerance, even though increasing at the boundaries of the investigated scan range. The impact on the beam size was limited for the upstream degrader, while dedicated strategies could be required to tackle the beam broadening through the local degrader. Range correction models were investigated for the upstream regulation. The impaired beam transport required a dedicated strategy for fine range control and compensation of beam intensity losses. Our current parameterization based on empirical data allowed energy modulation within acceptance with range errors (median 0.05 mm) and transmission (median –14%) compatible with clinical operation and remarkably low average 27 ms dead time for small energy changes. The technique, tested for the delivery of a skull glioma treatment, resulted in high gamma pass rates at 1%, 1 mm compared to conventional deliveries in experimental measurements with about 45% reduction of the energy switching time when regulation could be performed within acceptance. Conclusions: Fast energy modulation within beamline acceptance has potential for clinical applications and, when realized with an upstream degrader, does not require modification in the beamline hardware, therefore, being potentially applicable in any running facility. Centers with slow energy switching time can particularly profit from such a technique for reducing dead time during treatment delivery.